Use of chaos in key schedules for a symmetrical encryption algorithm without data loss - González-Ramírez, Marlon David; Vega-Alvarado, Eduardo; Morales-Rangel, Arturo (Nexo Revista Científica, 2023)
This research presents the construction of a symmetric encryption algorithm for images of pixels, in color and grayscale without loss of information and without compression, in BMP format. This algorithm consists of 15 rounds with S-box swapping, permutations, X-OR operations, and image size keys. The logistic map operation was used for the generation of S-boxes and to build a schedule of keys of the size of the image, the equations of E. Lorenz, transcendental numbers and the elliptic curve were used. To measure the strength of the encrypted result, the entropy of the information and the goodness test were used, obtaining favorable results and close to similar algorithms.